Temporal evolution and assessment of groundwater quality in coastal agricultural areas. The case of Pinios River Delta - Pisinaras, V; Ilias, A; Paraskevas, C; Poulos, S.; Matiatos, J.; Alexopoulos, J.; Kotsopoulos, S; Alexiou, I; Lazogiannis, K.; Arampatzis, G; Kalogianni, H; Tsekoura, D; et al. (10th International Hydrogeological Congress of Greece, 2014)
The present study aims to assess the current groundwater quality and investigate its temporal evolution in the two identified aquifers (shallow and deep) located in the sedimentary sequence of Pinios River estuary. Significant land use changes mark groundwater management practices of the shallow aquifer over the past years, as traditional crops of high water requirements have been partly substituted by less water demanding crops, and groundwater abstractions have been reduced and substituted by surface water from Pinios River to cover irrigation needs over a large part of the study area. To study the effect of aforementioned land use changes, major groundwater physicochemical parameter values for the year 2013 were assessed and compared to the corresponding data for the years 1998 and 1999. The results indicate that the quality of the shallow aquifer in terms of groundwater salinization and nitrate pollution may be considered as satisfactory with higher groundwater salt content observed in the northern and southern parts of the system. The water quality characteristics of the deep aquifer are overall worse than the shallow aquifer as groundwater salt content is increasing towards the coast. The temporal comparison of the water quality characteristics demonstrates no significant changes for seawater intrusion related parameters such as Electrical Conductivity, and Na+ and Cl- concentrations, but also for pollution related parameters such as NO3 - concentrations.